Online Learning of Children's Education Subject with Attention-Deficit Hyperactivity Disorder for Undergraduate Students of Special Education - Sri Joeda Andajani; Pamuji Pamuji (Department of Special Education, 2021)
This study aims to examine the effectiveness of online learning products of children's education subject with attention-deficit hyperactivity disorder for undergraduate students majoring in special education, faculty of Education at Universitas Negeri Surabaya. This study uses the ADDEM design model (Analyze, Design, Develop, Deliver, Evaluate, and Maintenance). The data collected in this study used a validation test technique of learning media experts and Special Education experts before the product was tested on students. The effectiveness test data were obtained from the results of studying midterm exams and final semester exams for undergraduate students in class A and B totaling 93 people majoring in special education. The product validity test results from the learning media validator have obtained a good rating score of 3.3 while an assessment from the Special Education validator has obtained a good score of 3.2. In the effectiveness testing period, it showed 78 midterm results of students with excellent grades, and 15 students with good grades. Likewise, the results of the final semester exams showed 45 students with excellent grades, and 48 students are good grades. Thus, it can be concluded that online learning of children's education subject with attention-deficit hyperactivity disorder in undergraduate students majoring in special education that is developed has the potential to improve learning outcomes.